Abnormal ear development in corn: A field survey. Issue 1 (1st February 2022) - Ortez, Osler A.; McMechan, Anthony J.; Hoegemeyer, Thomas; Rees, Jennifer; Jackson‐Ziems, Tamra; Elmore, Roger W.
Abstract: In July of 2016, abnormal ear development in corn ( Zea mays L.) (barbell‐ears, multiple ears per node herein termed as multi‐ears, and short‐husks) was reported in several cornfields that extended from the Texas Panhandle to eastern Colorado and East through Kansas, Nebraska, Iowa, and Illinois. Field surveys were conducted to study these ear abnormalities. Affected and unaffected plants were sampled from 15 farmer fields located in central and eastern Nebraska. Each plant was evaluated for ear type, ear placement, internode length, and grain yield. Along with plant evaluations, management practices and weather information were collected from the surveyed fields. Of the 15 surveyed fields, nine were grouped as affected (more than 10% abnormalities), and six were grouped as checks (<10% abnormalities). Affected fields averaged 26% of abnormalities, whereas check fields averaged only 4%. Ear abnormalities occurred on ears that seemed to be placed lower on plants relative to normal ears. Plants with abnormal ears had yield reductions between 35 and 91%, compared to plants with normal ears. Findings suggested that ear abnormalities may be a cumulative result from the classic genetic (hybrid‐specific), environmental (stress factors), and management interactions. The study of underlying causes for abnormal ear development in corn is imperative for understanding the likelihood of future events occurring and providing critical information to potentially manage and mitigate these issues. Core Ideas: Ear development issues in corn were reported in Nebraska and the region in 2016. Affected fields averaged 26% abnormal ears, up to 49% in a given field. Abnormal ears reduced yield, between 35 and 91% relative to normal ears. Abnormal ear placement seemed to be lower compared to normal ears. Ear abnormalities may be the cumulative result of classic G × E × M interactions.